Implementation of Late Payment Fines on TikTok PayLater: A Perspective of Islamic Economic Contract Law - Tri Aprinia Astutik; Saifuddin (Yayasan Azhar Amanaa Yogyakarta, 2026)
Study This use approach qualitative with method normative-juridical based studies bibliography . Methods This chosen because of research focus on analysis law to practice fine delay in TikTok PayLater service based on principle law Islamic economics , in particular draft ta'widh and gharamah . Study This aim analyze implementation fine delay in TikTok paylater service as one of the the growing Buy Now Pay Later (BNPL) system in ecosystem digital finance . Practice fine delay become issue important Because potential contain element usury , gharar , and cause injustice in perspective law agreement Islamic economics . Research results show that formally provisions​ fine has agreed in digital agreement , however in a way substantive its implementation potential Not yet fully in accordance with DSN-MUI fatwa No. 17/2000, especially related verification ability customers and transparency management of fine funds . Therefore that , is necessary more mechanisms​ clear and transparent so that implementation gharamah and ta'widh No deviate from principle justice in Islamic economics.